Nanoparticles coated with high molecular weight PEG penetrate mucus and provide uniform vaginal and colorectal distribution in vivo. (June 2016) - Maisel, Katharina; Reddy, Mihika; Xu, Qingguo; Chattopadhyay, Sumon; Cone, Richard; Ensign, Laura M; Hanes, Justin
Aim: We previously reported that nanoparticles (NPs) coated with 10 kDa PEG were mucoadhesive. Here, we demonstrate that by increasing the surface density, PEG with molecular weight (MW) as high as 40 kDa can be used as a mucoinert NP surface coating.Materials & methods: We compared two sets of reaction conditions for coating model polystyrene NPs with 10 kDa PEG and used optimized conditions to coat NPs with PEG as high as 40 kDa in MW. We then characterized NP transport in human cervicovaginal mucus ex vivo . We further administered PEG-coated NPs to the mouse cervicovaginal tract and colorectum to assess mucosal distribution in vivo .Results & conclusion: We demonstrate here that PEG with MW as high as 40 kDa can be densely grafted to the surface of NP to prevent interactions with mucus. NP coated with 10–40 kDa PEG rapidly diffused through human cervicovaginal mucus ex vivo, and uniformly lined the mouse colorectal and vaginal epithelium in vivo .